2014
DOI: 10.4103/2277-9531.145913
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the partner version of the multidimensional vaginal penetration disorder questionnaire: A tool for clinical assessment of lifelong vaginismus in a sample of Iranian population

Abstract: Background:The role of spousal response in woman's experience of pain during the vaginal penetration attempts believed to be an important factor; however, studies are rather limited in this area. The aim of this study was to develop and investigate the psychometric indexes of the partner version of a multidimensional vaginal penetration disorder questionnaire (PV-MVPDQ); hence, the clinical assessment of spousal psychosexual reactions to vaginismus by specialists will be easier.Materials and Methods:A mixed-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Increased fear of losing control during vaginal penetration in women with GPPPD (16) can reduce perceived penetration control and increase catastrophic pain recognition (17). A study on Iranian women with lifelong vaginismus showed that these women have similar experiences to women with sexual pain disorders (18). The effect of pain and pain prediction on the exacerbation of catastrophic thoughts and vaginal penetration fear are similar in women with sexual pain disorders (19).…”
Section: Discussionmentioning
confidence: 99%
“…Increased fear of losing control during vaginal penetration in women with GPPPD (16) can reduce perceived penetration control and increase catastrophic pain recognition (17). A study on Iranian women with lifelong vaginismus showed that these women have similar experiences to women with sexual pain disorders (18). The effect of pain and pain prediction on the exacerbation of catastrophic thoughts and vaginal penetration fear are similar in women with sexual pain disorders (19).…”
Section: Discussionmentioning
confidence: 99%
“…Based on an Iranian study, factors including male partner involvement during treatment and cultural background not influencing the treatment outcome, 32 whereas marital and fertility-related anxiety, family and social pressure, and personal guilt negatively affect the treatment outcome. 33 According to Anğin et al, 34 a positive history of vaginismus within a close family and environment negatively affects the treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the assessment of this construct is contained within instruments that assess several dimensions along with beliefs about vaginal penetration. For instance, instruments such as the Multidimensional Vaginal Penetration Disorder Questionnaire (MVPDQ) [5] and its partner version, Partner Version of the Multidimensional Vaginal Penetration Disorder Questionnaire (PV-MVPDQ) [6], include items involving attitudes and beliefs about vaginal penetration, but they do not assess these per se and are considered substantially long [7]. A shorter, more specific alternative can be found in the Vaginal Penetration Cognitions Questionnaire.…”
Section: Introductionmentioning
confidence: 99%